Verbal Parallelisms and Echo Effect in Nicander's Alexipharmaca - Żybert, Emilia (Polskie Towarzystwo Filologiczne, 2023)
The number of dis legomena in Nicander’s Theriaca and Alexipharmaca adds up 530 in 1588 lines in total. Among them, there are doublets that appear in each of the poems, and others that join them together. Moreover, there are multiple similarly sounding words placed close to each other, which create a kind of echo effect. In this article, I claim that the technique of duplicating words comes from repetition, which in turn is a characteristic of oral tradition. However, it was reworked by Hellenistic poets, most importantly by Aratus, and then adapted and developed by others, including Nicander. Firstly, based on the introductory and ending lines of the Alexipharmaca, I discuss a wide spectrum of doubled words used in the poem, focusing on Nicander’s dialogue with earlier literature. Secondly, I attempt to strengthen Enrico Magnelli’s argument that the ending of the poem (611–628), believed to be spurious by Nicander’s editors, is in fact authentic.